Characterization of health concerns in people with neurofibromatosis type 1. Issue 1 (28th November 2022) - Fleming, Jane; Morgan, Oliver; Wong, Claire; Schlub, Timothy E.; Berman, Yemima
Abstract: Background: Neurofibromatosis 1 (NF1) is a common cancer predisposition syndrome. Affected individuals require lifelong surveillance and often suffer progressive disfigurement due to cutaneous neurofibromas. The aim of this research was to characterize health concerns and quality of life (QOL) in a population cohort. Methods: An online survey was completed by 68 adults and 32 parents of children with NF1, and 60 controls. The survey included the Skindex‐29 QOL scale, 5D‐itch scale, and additional health questions. Results: Frequency of itch was high in children (50%) and adults (69%), with most expressing interest in treatment for itch. The presence of itch and increased visibility of NF1 were predictors of poorer QoL. Many adults (53%) and parents (44%) desired access to treatment to improve cosmetic appearance. Muscle weakness/tiredness was also prevalent amongst (60–70%) adults and children with NF1. Two‐thirds of adults with NF1 reported limited awareness of NF1 services and poor knowledge of surveillance, particularly breast screening in young women. Conclusion: This study highlights the impact of NF1‐related itch and visibility in adults and children with a need for cosmetic and itch treatment. The findings emphasize a need for strategies to promote awareness, and access to management and treatment of NF1 in adults. Abstract : NF1 is a common cancer predisposition syndrome that requires lifelong surveillance. The aim of this research was to characterize health concerns and QoL in a population cohort. This study highlights that the presence of itch and increased visibility of NF1 complications impacts the QoL of adults and children.